Mind, brain, and free will - Swinburne, Richard (Oxford : Oxford University Press, 2013)
Richard Swinburne presents a powerful case for substance dualism and libertarian free will. He argues that pure mental and physical events are distinct, and defends an account of agent causation in which the soul can act independently of bodily causes. We are responsible for our actions, and the findings of neuroscience cannot prove otherwise.
Description based on online resource; title from home page (viewed on Jan. 7, 2013).
Includes bibliographical references and index.
Keywords: Free will and determinism